The role of E-learning in institutions of higher education in achieving the goals of sustainable development in Jordan. - Areej Derbas; Hani Y Ayyoub; Tasneem Hyarat; Adnan Hnaif; Raed Al-Quraan; Amani Al-Serhan; Marwan Al-Tawil; Aida Al-Awamleh; Walaa Quteshat; Ismail Al Zyoud (PLoS ONE)
E-learning plays an important role in achieving the Sustainable Development Goals (SDGs). This research aimed to E-Learning's impact on attaining SDGs in Jordanian Higher Education with a primary focus on the University of Jordan as a case study. The study was conducted on a sample of 3,000 students at the University of Jordan from various majors and academic levels and for both genders. The study adopted the quantitative statistical analysis method where a questionnaire was distributed electronically to students through the official platforms approved by the university. The results of the research showed that there is a positive role for E-learning in Higher Education institutions in achieving the sustainable development goals in Jordan, especially SDGs (1, 2, 4, 5, 7, 8, 9, 11, 12, 15, 16 and 17). Through the university's efforts to develop the skills of students and faculty members in the field of technology and innovation, and holding seminars and conferences via E-learning platforms that enable universities to disseminate valuable information, participate in open dialogues, and raise awareness about SDGs and how to achieve them. Despite these efforts, more remain required to work towards the achievement of SDGs (3, 6, 10, 13, and 14).